BENTUK KATA KERJA INFLEKSI BAHASA INGGRIS DAN BAHASA MELAYU MANADO (ANALISIS KONTRASTIF) - Jansen, Frieda Theresia (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Language is a tool of communication. English and Manado Malay Language are two languages of different families. English belongs to Indo-European language whereas Manado Malay language belongs to Austronesian language. This research used descriptive method through contrastive approach. The aim of this research in to find out the description about the similarities and differences of inflectional verbs ssform between English and Manado Malay Language. The theories used in this research are taken from Frank (1972), Gleason (1962) about inflectional verb form in English and concepts of karisoh-Najoan about inflectional verb form in Manado Malay Language.